A Real-time Emotion Recognition System Based on an AI System-On-Chip Design - Li, Wei-Chih; Yang, Cheng-Jie; Fang, Wai-Chi (2020 International SoC Design Conference (ISOCC), 2020)
In this paper, we developed and integrated a realtime emotion recognition system using an AI system-on-chip design. The emotion recognition platform combined three different physiological signals, Electroencephalogram (EEG), electrocardiogram (ECG), and photoplethysmogram (PPG) as the classification resources. A 3-to-1 Bluetooth piconet was deployed to transmit all physiological signals on a single platform access point and to make use of low power wireless technologies. The system then integrated an AI computing chip with a convolution neural network (CNN) structure to classify three emotions, happiness, anger, and sadness. The average accuracy for a subject-independent classification reached 72.66%. The proposed system was integrated with the RISC-V processor and AI SOC to implement real-time monitoring and classification on edge.